MATA KULIAH HUKUM DIANTARA PROGRAM STUDI PENDIDIKAN KEWARGANEGARAAN DENGAN PROGRAM STUDI HUKUM - Alamsyah Basri (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT The implementation of law courses at the Teacher Training and Education Faculty Citizenship Education Program has many similarities with the law study Program. But it also has a striking difference between the two. So that the limitation of delivering law course material in the Citizenship Education Study Program is needed. So that the Learning Implementation Plan (RPP) and Semester Learning Plan (RPS) can be made proportionally. For this reason, knowing the limitations and adjustments of this law course should be emphasized and clarified. This study uses a library method (desk research) with a Normative Juridical Research approach. From the results of the discussion of this study, it was found that Graduate Learning Outcomes (CPL) became the basis for determining the required boundaries. For this reason, the role of law courses at the Teacher Training and Education Faculty of Citizenship Education Study Program must be directed to get graduates who have the attitude and character of the Indonesian nation who believe and fear God Almighty, have noble character, have noble character, have noble character, have noble character. . healthy, knowledgeable, capable, creative. , be independent, and become democratic and responsible citizens as stipulated in the National Education Goals Keywords: Law Studies Courses; Learning Outcomes of Graduates, National Education Goals